Assessment of the Immunohistochemical expression of EBV in oral lichen planus - Tania A Al-Tahan; Ahlam H Majeed (College of Dentistry/ University of Baghdad, 2015)
Background: Oral lichen planus (OLP) is a chronic immunologic disease. The etiology of OLP is unknown, viral antigens (for example EBV) have been proposed as etiologic agents. OLP may get transformation to malignancy so research on the presence of these in OLP lesions seems to be necessary. The aim of this study was to evaluate EBV expression immunohistochemically in OLP. Materials and Methods: Tissue specimens of 30 formalin fixed, paraffin-embedded tissue Blocks histologically diagnosed oral lichen planus was performed to evaluate EBV expression. Results: Expression of EBV was detected in epithelium of (46.6%) in the study samples in (OLP). no statistically significant correlation was found with clinical parameters except for a significantly higher expression in females. Conclusions: Epstein Barr viruses were present in considerable amounts in oral lichen planus. Taking into account the potential of viruses in OLP proving or disapproving or etiological role of viruses in OLP is continuously need to be examined in further studies.